2006
DOI: 10.1186/1472-6963-6-152
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and hospital utilization among younger adult pneumonia admissions at a Canadian hospital

Abstract: Background: Although the general association between socioeconomic status (SES) and hospitalization has been well established, few studies have considered the relationship between SES and hospital length of stay (LOS), and/or hospital re-admission. The primary objective of this study therefore, was to examine the relationship of SES to LOS and early re-admission among adult patients hospitalized with communityacquired pneumonia in a setting with universal health insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
1
22
2
Order By: Relevance
“…Jasti et al 22 reported increased risk of readmission for patients with lower education and who were unemployed. McGregor et al 23 found an increased risk of readmission for lower income patients. Of the two studies that assessed Level 3 factors, no association was seen for nursing home residence 19 or rurality.…”
Section: Social Factors Associated With Readmission In Pneumoniamentioning
confidence: 98%
“…Jasti et al 22 reported increased risk of readmission for patients with lower education and who were unemployed. McGregor et al 23 found an increased risk of readmission for lower income patients. Of the two studies that assessed Level 3 factors, no association was seen for nursing home residence 19 or rurality.…”
Section: Social Factors Associated With Readmission In Pneumoniamentioning
confidence: 98%
“…A French study found low socioeconomic status was an independent predictor of significantly longer hospitalization [10], but other reports found no relationship [11]. Jasti et al .…”
Section: Introductionmentioning
confidence: 99%
“…Because data on gross available family income per inhabitant were only available for municipalities with >5000 inhabitants, the mean income of the neighbouring municipalities was applied where data were lacking (McGregor et al, 2006). Two municipalities were considered neighbouring if they shared geographical limits (first order neighbouring municipalities).…”
Section: Methodsmentioning
confidence: 99%